Global value chains, the rise of the robots and human capital - Dalia Marin (Wirtschaftsdienst, 2018)
It is often argued that robots will lead to the reshoring of activity from low wage countries to rich countries - the revival of manufacturing in rich countries. But smart robots are a capital biased technology which could potentially replace smart people. As a result the skill premium - the relative wage between a university graduate and a high school graduate - is declining in Europe. The expansion of higher education has been too aggressive in face of the capital bias of digital technology. – – This essay examines whether robots will lead to the reshoring of activity from low-wage countries to rich countries, leading to a revival of manufacturing in rich countries. I argue that reshoring will not lead to an employment boom in rich countries, because the brilliant robots are a capital-biased technology, and as such, they potentially replace smart people. As a result, the skill premium - the wage discrepancy between a university graduate and a high school graduate - is declining in Europe. I argue further that the expansion of higher education has been too aggressive in light of the capital bias of digital technology.
Keywords: F1; O3; D23; 330